Prolonged elevations in haemostatic and rheological responses following psychological stress in low socioeconomic status men and women - Steptoe, Andrew; Kunz-Ebrecht, Sabine; Rumley, Ann; Lowe, Gordon D.O. (Thrombosis and Haemostasis, 2003)
Low socioeconomic status (SES) and psychological stress are associated with increased risk of coronary heart disease, and both may influence haemostatic responses. Von Willebrand factor (vWF), Factor VIII, plasma viscosity, haematocrit, blood viscosity, tissue plasminogen activator (t-PA) and fibrin D-dimer were measured at rest and following stressful tasks in 238 middle-aged British civil servants. SES was defined by grade of employment. Lower SES was associated with higher resting vWF, Factor VIII and plasma viscosity. Psychological stress stimulated increases in haemostatic and rheological factors. Initial stress responses did not vary with SES, but Factor VIII, plasma viscosity and blood viscosity remained more elevated 45 minutes post-stress in lower SES participants. High blood pressure stress reactivity was also associated with greater haemostatic responses. We conclude that lower SES is characterised by more prolonged elevations in procoagulant responses following psychological stress, and that these processes might contribute to increased cardiac risk.
Keywords: Socioeconomic status; haemostatic factors; psychological stress; behaviour